Pengenalan Tumbuhan Lokal Untuk Kosmetik Kepada Gen Z : Edukasi Formulasi Sediaan Pomade Estrak Daun Meniran ((Phyllanthus Niruri L ) Sebagai Perangsang Penumbuh Rambut - Syafitri, Anggun; Rahmi, Sofia; Tamba, Agnes Clara; Hayati, Silmi (Jurnal Pengabdian Masyarakat Putri Hijau, 2024)
Health Vocational High School is a place of education where students study. Busy student activities can sometimes reduce students' knowledge regarding the use of natural materials. The method applied in community service activities is providing counseling and education in the form of lectures and questions and answers directly by practicing making pomade cosmetics. Students' lack of knowledge regarding the use of natural ingredients from meniran leaves (Phyllanthus niruri L) as the main ingredient in natural pomade cosmetics which functions as a hair growth stimulant. For this reason, students are given education and understanding about the formulation of meniran leaf extract pomade preparations. The aim of holding service activities for students is "Introducing Local Plants for Cosmetics to Gen Z: Education on the Formulation of Meniran Leaf Extract Pomade Preparations as a Hair Growth Stimulator". To provide knowledge and understanding to Dewantara Husada Health Vocational School students regarding the introduction of local plants for cosmetics in the formulation of meniran leaf extract pomade as a hair growth stimulant. The conclusion of this PKM activity was carried out using the lecture and question and answer method, and practice. Based on the high level of participation in this PKM activity, it was classified as very good, participants in the question and answer session were considered to have a special interest in the material